2014
DOI: 10.1093/annonc/mdu036
|View full text |Cite
|
Sign up to set email alerts
|

‘An ounce of prevention is worth a pound of cure’: the case for and against GnRH-agonist for fertility preservation

Abstract: The late effects of cancer treatment have recently gained a worldwide interest among reproductive endocrinologists, oncologists, and all health-care providers, and the protection against iatrogenic infertility caused by chemotherapy assumes a high priority. Here, we summarize the case for and against using GnRH-agonist for fertility preservation and minimizing chemotherapy-induced gonadotoxicity. The rationale and philosophy supporting its use is that preventing premature ovarian failure (POF) is preferable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
105
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 55 publications
2
105
0
1
Order By: Relevance
“…The OR for preserving COF was 6.87 for the patients who received GnRHa in addition to chemotherapy (95% CI 3.4-13.4) and 3.12 (95% CI 1.7-5.8) (p , .001) for spontaneously conceiving versus those who were treated with chemotherapy without the GnRHa. Although, 25 studies (over 10 prospective RCTs) have shown a significant decrease in POF rate in survivors of chemotherapy and GnRHa, and there are nine publications not supporting GnRHa use [1].The ASCO [5], the ASRM [6], and the ESMO [7] do not support GnRHa as a proven method for fertility preservation and consider it experimental. One of the main arguments against considering the GnRHa cotreatment as an established method for fertility preservation is that preserving COF and regular menses in survivors is only a surrogate marker not equivalent to fertility, that is, pregnancies [10].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The OR for preserving COF was 6.87 for the patients who received GnRHa in addition to chemotherapy (95% CI 3.4-13.4) and 3.12 (95% CI 1.7-5.8) (p , .001) for spontaneously conceiving versus those who were treated with chemotherapy without the GnRHa. Although, 25 studies (over 10 prospective RCTs) have shown a significant decrease in POF rate in survivors of chemotherapy and GnRHa, and there are nine publications not supporting GnRHa use [1].The ASCO [5], the ASRM [6], and the ESMO [7] do not support GnRHa as a proven method for fertility preservation and consider it experimental. One of the main arguments against considering the GnRHa cotreatment as an established method for fertility preservation is that preserving COF and regular menses in survivors is only a surrogate marker not equivalent to fertility, that is, pregnancies [10].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the late effects of cancer treatment have recently gained a worldwide interest [1][2][3][4], and the protection against iatrogenic infertility caused by chemotherapy assumes a high priority. Resumption of menses may not be an accurate marker of fertility, because infertility and diminished ovarian reserve are observed in women who resume normal menstrual cycles after treatment with chemotherapy [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations